PENGARUH CORPORATE GOVERNANCE TERHADAP AGENCY COST PADA PERUSAHAAN PERBANKAN DI INDONESIA: THE INFLUENCE OF CORPORATE GOVERNANCE ON AGENCY COSTS IN INDONESIAN BANKING COMPANIES - Fransisca, Theresia Adelia; Kusumaningtias, Rohmawati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The research aims to determine the impact of the connection between corporate governance and agency expenses. The study's independent variables include the audit committee, management ownership, board of commissioners, and debt policy. The dependent variable used in this study is agency cost, which is computed using asset characteristics. This study also uses a control variable, namely company size. The population data used in this study are the banks registered on the Indonesia Stock Exchange between 2017 and 2021. Sampling technique using purposive sampling. The results of this study suggest that agency expenses are influenced by the board of commissioners and firm size. In contrast, there is no connection between the audit committee, management ownership, and debt policy, and agency expenses. The implication of this research is to minimize losses caused by the actions and policies of agents, principals are expected to continue to monitor the implementation of good corporate governance